1998
DOI: 10.1159/000010010
|View full text |Cite
|
Sign up to set email alerts
|

Placenta praevia and accreta: Analysis of a Two-Year Experience

Abstract: Objective: Our purpose was to determine the relationship between previous caesarean section and subsequent development of placenta praevia and placenta praevia with accreta. Method: A retrospective review of the case records of all women delivered with the diagnosis of placenta praevia during the 2-year period from January 1, 1995, to December 31, 1996, at the tertiary referral centre, Princess Badeea Teaching Hospital, in north Jordan. Results: There were 18,651 deliveries in the study period. 65 (0.35%) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…We have already referred to the high prevalence of placenta previa and accreta in women with multiple Cesarean sections1–5. In 10 of 14 cases (71%) of first‐trimester Cesarean scar pregnancies reported in the literature, the authors observed that the pregnancy penetrated deep into the myometrium (Table 1).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have already referred to the high prevalence of placenta previa and accreta in women with multiple Cesarean sections1–5. In 10 of 14 cases (71%) of first‐trimester Cesarean scar pregnancies reported in the literature, the authors observed that the pregnancy penetrated deep into the myometrium (Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…In women with a history of multiple Cesarean sections the incidence of placenta previa is ten times higher compared with women who had vaginal deliveries2. When the placenta is implanted over the uterine scar, it is abnormally adherent in 30–40% of cases, which often causes uncontrollable hemorrhaging at delivery2, 3. Abnormally inserted placentae are responsible for 50–65% of all obstetric hysterectomies, 66% of which have a history of previous Cesarean sections4, 5.…”
Section: Introductionmentioning
confidence: 99%
“…The risk increased as the number of previous CSs increased (Ziadeh et al, 1999). The incidence of placenta praevia in association with 4 or more previous caesareans was five times the general obstetric population.…”
Section: Discussionmentioning
confidence: 88%
“…The reported prevalence of placenta previa [14,15,16,17] varies from 0.4 to 0.6%. The incidence is increasing mainly due to the high CS rate [18,19], as well as the rising number of assisted reproductive technique procedures [20,21].…”
Section: Discussionmentioning
confidence: 99%